The Lasting Influence of a Peer-led Adolescent Relationship Abuse Prevention Program on Former Peer Leaders' Relationships, Identities, and Trajectories in Emerging Adulthood. Issue 9 (May 2022) - Johnson, Natalie Penhale; Sundaram, Mangai A.; Alder, Jess; Miller, Elizabeth; Ragavan, Maya I.
Adolescent relationship abuse (ARA) has well-documented detrimental health effects. Adolescence is a window of opportunity to promote development of healthy relationship behaviors. Although peer-led interventions have a history of use in the health education field, there are few rigorously evaluated peer-led interventions targeting ARA. Start Strong leverages peer support by training adolescents to deliver ARA prevention curriculum to younger peers. Although the program has shown positive results in recipients, little is known about the impact on the peer leaders themselves. This qualitative study describes the impact of being an ARA prevention peer leader on former peer leaders' relationships and trajectories in emerging adulthood. Specific objectives include: (a) how being a peer leader shaped participants' norms around romantic relationships and ARA, and (b) the impact of participating in a peer leadership program on their emerging adult lives. Researchers conducted semi-structured interviews with former peer leaders and coded transcripts using thematic analysis. Fourteen former peer leaders aged 18–26 participated. Most participants (99%) identified as Black or Afro-Latinx. Participants described a lasting impact on their relationships, identity formation, future orientation, and professional lives. Participants highlighted the skills they use to avoid unhealthy relationships and help friends and family navigate their relationships. They identified unexpected challenges, including a sense of isolation around how their relationship expectations differ from same-aged peers, and trepidation about dating partners without advanced healthy relationship knowledge. Participants highlighted positive impacts beyond those pertaining to relationships, including their identity development and expanded sense of opportunity. Finally, they identified tangible skills gained from program participation and relevance to their professional paths. This study suggests that peer-led ARA prevention programs have a far-reaching impact on participants' lives that lasts into adulthood. Future studies may examine how professional development within peer-led interventions can influence future orientation and thus bolster protective factors against ARA.